1981
DOI: 10.1104/pp.67.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, Growth, and Ultraviolet Irradiance Absorbance of Cucurbita pepo L. Leaves Exposed to Ultraviolet-B Radiation (280-315 nm)

Abstract: Net photosynthesis, growth, and ultraviolet (UV) radiation absorbance were determined for the first leaf of Cucurbita pepo L. exposed to two levels of UV-B irradiation and a UV-B radiation-free control treatment. Absorbance by extracted flavonoid pigments and other UV-B radiationabsorbing compounds from the first leaves increased with time and level of UV-B radiation impnging on leaf surfaces. Altbough absorbance of UV-B radiation by extracted pigments increased substantially, UV-B radiation attenuation appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…A significant reduction in leaf area was observed in several horticultural crops such as cucumber and radish (Tevini et al, 1983). Also, sunflower (Tevini and Teramura, 1989), pumpkin (Cucurbita pepo L.) (Sisson, 1981) and field crops such as soybean (Teramura and Murali, 1986) had less leaf area when exposed to UV-B. In the present study, plants treated with UV-B radiation had a significantly smaller canopy leaf area.…”
Section: Effects Of Uv-b On Cotton Growthmentioning
confidence: 51%
“…A significant reduction in leaf area was observed in several horticultural crops such as cucumber and radish (Tevini et al, 1983). Also, sunflower (Tevini and Teramura, 1989), pumpkin (Cucurbita pepo L.) (Sisson, 1981) and field crops such as soybean (Teramura and Murali, 1986) had less leaf area when exposed to UV-B. In the present study, plants treated with UV-B radiation had a significantly smaller canopy leaf area.…”
Section: Effects Of Uv-b On Cotton Growthmentioning
confidence: 51%
“…Reduction in whole plant biomass, plant height and expansion growth of leaves/cotyledons has been observed by elevated and ambient levels of UV-B radiation in several plant species. 18,19,20,109 UV-B caused reduction in the expansion of cotyledons has been observed in soybean, 110 Cucurbita pepo, 111 and Datura ferox, 112 cowpea 113 and cucumber. 3,28,114,115 CKs like BAP, Furfuryl amino purine (FAP), Zeatin and thidiazuron (TDZ) promoted the expansion growth of cucumber cotyledons in the darkness and exposure of cotyledons to UV-B inhibited the CKs-induced expansion growth, which varied with the type of cytokinins used; inhibition was found more in FAP and zeatin compared to BAP and TDZ.…”
Section: Interaction Of Cytokinins With Uv-b Stressmentioning
confidence: 98%
“…Murali and Teramura (20) reported a masking of UV-B radiation effects in drought-stressed soybean and attributed this to anatomical (leaf thickening) and biochemical (flavonoid production) changes induced by drought stress. However, other studies have observed deleterious effects of UV-B radiation in the presence of leaf thickening and elevated flavonoid concentrations (18,24,26). Thus alternative explanations should also be considered.…”
mentioning
confidence: 99%